A case of latex allergy caused by hypersensitivity to spacer with mask in a 6-year-old boy with asthma - Kiliç, Mehmet; Altintaş, Derya Ufuk; Yilmaz, Mustafa; Kendirli, Seval Güneşer; Karakoç, Gülbin Bingöl (My University, 2009)
The prevalence of latex allergy in children is increasing worldwide. Contact urticaria is a type I hypersensitivity reaction mediated by immunoglobulin E that usually manifests as localized erythema, edema, pruritus, and urticarial plaques. It can also cause systemic reactions, including anaphylaxis. In this report, we describe a child with asthma who was found to have type I hypersensitivity to rubber by prick test. A six-year-old boy was admitted to our clinic with complaints of erythema, pruritus, and urticarial plaques on the edge of his mouth for the previous 10 days. Latex allergy was suspected. Skin prick test showed a positive reaction to latex. Physicians should be aware of latex allergy in atopic children, especially in those using spacer with a mask.
Alti yaşinda astimli erkek bir hastada araci tüp maskesine ba?li gelişen lateks alerjisi
Keywords: Asthma; Childhood; Latex allergy; Spacer with mask